The Effect of H-Bonding on Radical Copolymerization of Maleic Anhydride with N-tert-Butylacrylamide and Its Characterization - Ahmet Okudan; Ayşe Karasakal (International Journal of Polymer Science)
The copolymerization reaction between N-tert-butylacrylamide (NTBA) and maleic anhydride (MA) in p-dioxane solution at 65°C using 2,2′-azoisobutyronitrile (AIBN) as an initiator in nitrogen atmosphere was carried out. The chemical structure of the obtained copolymers from a wide range of monomer feeds was determined by elemental analysis (content of N for NTBA units), Fourier transform infrared (FTIR), and 1H-NMR spectroscopy. Also, the amounts of MA units in the copolymers were found using the chemical titration method. An observed tendency toward alternating copolymerization at ≤50 mol% NTBA concentration in monomer feed and relatively high activity of NTBA growing radical was explained by H-bond formation between C=O (anhydride) and NH (amide) fragments during chain growth reactions. Intrinsic viscosity and the molecular weights of the synthesized copolymers depend on the type of comonomer and the amount of NTBA units in the copolymers. The synthesized poly(NTBA-MA)s containing a functional amphiphilic group show both temperature and pH sensitivity and can be used for biological proposes as a physiologically active macromolecular system.